Desain Kebijakan Pulau Harapan dalam Pengembangan Wisata Bahari dengan Menggunakan Interpretative Structural Modeling - Naomi Heumasse; Rosmawaty Anwar; Nungky Puspita (Journal of Tourism Destination and Attraction, 2014)
Evaluation of the policy on Pulau Harapan through the development of marine tourism was deemed necessary to be done in order to develop a design or model of appropriate, efficient, effective and sustainable policies. However, the extent of the impact of marine tourism development for socio-economic life and well-being of local communities in this tourist destination is still not known with certainty and depth. ISM is a methodology that can help to identify the relationship between the idea desicive structures in a complex problem. ISM method is used to analyze the relationship and dependencies among the elements that make up the structure of marine tourism development design in Pulau Harapan. From the discussion, the experts then identified five critical factors that need to be studied, namely the elements of the program requirements, a major obstacle, the public sector is involved, goals and institutions involved. These five elements can minimize constraints that exist because they are supported by a program requirement, also with the involvement of the institution, as well as the involvement of influential community that marine tourism destination development program will achieve.